Exploring the potential of cartilage tissue engineering to restore joint damage - Sha'ban, Munirah; Johnson, Susan Doan (OrthopaedicsOne, 2011)
Joint damage, articular cartilage degeneration, and the research into methods of restoring the articulation surfaces are not new topics of interest. For centuries, clinicians and scientists have recognized the importance of cartilage damage, and learned about the normal form and function of articular cartilage, as well as the process of degradation and restoration. Unfortunately, only some of the real problems have been resolved.